Comparison of Execution in Warranty and Fiduciary Bank - Lilawati Ginting (RIRAI Publisher, 2022)
The types of guarantee institutions known in the Indonesian legal system can be classified according to their type, nature, purpose and management. Late payment will result in a claim for the guaranteed goods. Execution is an attempt by the ruling party to seek justice through res judicata. Bank guarantees, which are individual guarantees, and trustees, which are physical guarantee institutions, have different implementation methods at the time of default. This study tries to explain the problem of comparing legal situations with bank guarantees and trustees in a normative and juridical way. The results show that The authority to enforce bank guarantees on assets belonging to debtors in default refers to Articles 1131 and 1132 of the Civil Code. According to Articles 1131 and 1132 of the Civil Code, the goods belonging to the debtor (the guarantor) are generally collateral for the debtor's debt, and the proceeds from the sale of the collateral are charged to the recipient of the guarantee.